Mammary Gland Evaluation in Juvenile Toxicity Studies: Temporal Developmental Patterns in the Male and Female Harlan Sprague-Dawley Rat. (October 2016) - Filgo, Adam J.; Foley, Julie F.; Puvanesarajah, Samantha; Borde, Aditi R.; Midkiff, Bentley R.; Reed, Casey E.; Chappell, Vesna A.; Alexander, Lydia B.; Borde, Pretish R.; Troester, Melissa A.; Bouknight, Schantel A. Hayes; Fenton, Suzanne E.
There are currently no reports describing mammary gland development in the Harlan Sprague-Dawley (HSD) rat, the current strain of choice for National Toxicology Program (NTP) testing. Our goals were to empower the NTP, contract labs, and other researchers in understanding and interpreting chemical effects in this rat strain. To delineate similarities/differences between the female and male mammary gland, data were compiled starting on embryonic day 15.5 through postnatal day 70. Mammary gland whole mounts, histology sections, and immunohistochemically stained tissues for estrogen, progesterone, and androgen receptors were evaluated in both sexes; qualitative and quantitative differences are highlighted using a comprehensive visual timeline. Research on endocrine disrupting chemicals in animal models has highlighted chemically induced mammary gland anomalies that may potentially impact human health. In order to investigate these effects within the HSD strain, 2, 3, 7, 8-tetrachlorodibenzo -p -dioxin, diethylstilbestrol, or vehicle control was gavage dosed on gestation day 15 and 18 to demonstrate delayed, accelerated, and control mammary gland growth in offspring, respectively. We provide illustrations of normal and chemically altered mammary gland development in HSD male and female rats to help inform researchers unfamiliar with the tissue and may facilitate enhanced evaluation of both male and female mammary glands in juvenile toxicity studies.